Therapeutic effects and mechanisms of N-(9,10-anthraquinone-2-ylcarbonyl) xanthine oxidase inhibitors on hyperuricemia - Tianshu Gao; Jin Xu; Yuxiao Xiao; Jiaqi Li; Weifeng Hu; Xiaoyu Su; Xudong Shen; Wan Yu; Zhen Chen; Baosheng Huang; Honglei Li; Xing Wang (Frontiers Media S.A., 2022)
Objective: To observe the antioxidative effects of N-(9,10-anthraquinone-2-ylcarbonyl) xanthine oxidase inhibitors (NAY) in vitro and in vivo models of hyperuricemia and explore the mechanism.Methods: A classical experimental method of acute toxicity and a chronic toxicity test were used to compare the toxic effects of different doses of NAY in mice. The hyperuricemia mouse model was established by gavage of potassium oxonate in vivo. After treatment with different doses of NAY (low dose: 10 mg/kg, medium dose: 20 mg/kg, and high dose: 40 mg/kg) and allopurinol (positive drug, 10 mg/kg), observe the levels of uric acid (UA), creatinine (CRE), and urea nitrogen (BUN) in urine and serum, respectively, and detect the activities of xanthine oxidase in the liver. The hyperuricemia cell model was induced by adenosine and xanthine oxidase in vitro. The cells were given different doses of NAY (50, 100, and 200 μmol/L) and allopurinol (100 μmol/L). Then the culture supernatant UA level of the medium was measured. The next step was to detect the xanthine oxidase activity in the liver and AML12 cells, and the levels of tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), interleukin-1β (IL-1β), and NOD-like receptor thermal protein domain-associated protein 3 (NLRP3) inflammatory factors in the kidney and serum of mice. Western blot was used to detect xanthine oxidase protein expression in mouse liver tissue and AML12 cells, ASC, Caspase-1, NLRP3, GLUT9, OAT1, and OAT3 protein expression in mouse kidney tissue and HK-2 cells. Hematoxylin-eosin staining was used to stain the liver and kidney tissues of mice and observe the tissue lesions.Results: NAY had little effect on blood routine and biochemical indexes of mice, but significantly reduced the serum UA level. NAY significantly reduced the level of UA in hyperuricemia mice and cells by inhibiting xanthine oxidase activity and reduced the levels of TNF-α, IL-6, and other inflammatory factors in serum and kidney of mice. NAY can inhibit inflammation by inhibiting the NLRP3 pathway. In addition, NAY can downregulate GLUT9 protein expression and upregulate OAT1 and OAT3 protein expression to reduce the UA level by promoting UA excretion and inhibiting UA reabsorption.Conclusion: These findings suggested that NAY produced dual hypouricemic actions. On the one hand, it can inhibit the formation of UA by inhibiting xanthine oxidase inhibitors activity, and on the other hand, it can promote the excretion of UA by regulating the UA transporter. It provides new ideas for the development of hyperuricemia drugs in the future.